PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS II SD NEGERI 010 SILIKUAN HULU KECAMATAN UKUI - Suharni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The problem in this research is the low student learning outcomes in Civics (PKn) in class II SD Negeri 010 Silikuan Hulu, which amounted to 65.33. Based on this, researchers conducted a study with the aim to improve student learning outcomes in PKn through the implementation of the STAD (Student Teams Achievement Divisions) type cooperative learning model. This research is a classroom action research conducted over two cycles, consisting of two meetings and a daily test in each cycle. The data collection technique used is the technique of observing activities of teachers and students and learning outcomes in PKn. The analysis technique used is descriptive analysis. The results showed that the application of the STAD cooperative learning model can increase the learning outcomes of students in PKn class II. This is supported by: (1) the activities of teachers has increased. In the first cycle, the first meeting obtained a score of 19 or 76.00% in the